Behaviourally informed approach to corporate criminal law: Ethicality as efficiency - Korkka-Knuts, Heli (Bergen Journal of Criminal Law & Criminal Justice, 2022)
An extensive body of behavioural evidence suggests that our actions are not primarily steered by threats of sanction but, instead, by morals, habits, and social norms. This proposition applies equally in corporate environments. Yet, corporate criminal law has traditionally relied on fear of sanctions and deterrence as the prevailing theoretical guidance. This article argues that this line of thinking leads to misinformed regulatory results because of a misguided behavioural assumption of an amoral calculative individual. To bridge the gap between the accumulated behavioural data and doctrinal corporate criminal law, this article suggests a novel behaviourally informed corporate crime prevention theory. Instead of solely concentrating on deterrence and threats of sanction, modern corporate criminal policy should favour regulatory designs that incentivise ethics-based corporate compliance structures that make use of morals as efficient behavioural constraints. Based on the findings of this article, this is best attained by adopting a guilt-based corporate criminal liability model recognising a corporation as a moral actor capable of ethical considerations.